The effect of a Technology-Enhanced Learning (TEL) module on the achievement of form four students in the topic of waves and sound - Norfazilah Mohamad Yusuf (2020)
The purpose of this study was to determine the effect of a technology-enhanced learning (TEL) module on the achievement of form four students in the topic of waves and sound. Constructivism was used as an underpinning theory in the development of the contents of TEL module. In terms of module development, the Sideks model was used that has nine steps to produce a completed draft module. True-experimental design was used to determine the effect of the module. Instrument comprised a pre and post-test. The validity of the module and the instrument was verified by three experts in the field. The instrument has a relatively high reliability based on Cronbach alpha coefficient which was = 0.81. A sample of 60 form four physics students were selected and assigned randomly into a control group (n=30) and an experimental group (n=30). The treatment for the experimental group was conducted for four weeks. In the pilot study, the experts agreed that the TEL module has had a high content validity with 90% agreement among the three experts. The result of the independent sample t-test [t (58) = -5.53, p < 0.05] showed that the achievement of the students in the experimental group (M = 70.33, SD =10.31) was significantly higher than the students in the control group (M = 55.53, SD = 10.42). In conclusion, the main finding showed that the TEL module was effectivein enhancing the students achievement in the waves and sound topic. This studyimplicates that the TEL module could be used by physics teachers in other secondary schools in Malaysia.